MASA DEPAN MEDIA KOMUNIKASI DAKWAH - Hawirah; Asriadi, Asriadi; Yuliana; Aswandi, Syawal; Yumi, Sri (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2025)
The development of information and communication technology has brought about major changes in the way da'wah is delivered and received by society. Da'wah communication media is no longer limited to mosque pulpits and direct lectures, but has spread to social media, digital platforms, and various internet-based technologies. This study aims to examine how the future of da'wah communication media is influenced by technological developments and how da'wah strategies can adapt to the digital era. Using the literature review method, this study analyzes various literatures that discuss contemporary da'wah, digital communication, and the challenges and opportunities of da'wah in the future. The results of the study show that the success of da'wah in the future is highly dependent on the ability of da'i and da'wah institutions to understand the characteristics of digital media, build relevant content, and apply an interactive and personal communication approach. Therefore, the transformation of da'wah strategies is a necessity so that Islamic messages remain alive and effective in the lives of modern society.